Dimension Wise Difference in Planning Instructional Strategies at Secondary Level in Pakistan - Sidra Rizwan, (JCTE, 2023)
The article focuses on planning instructional strategies (PIS) with its three dimensions namely understanding, dispositions and practices as reported in the “National professional standards for teachers in Pakistan” (NPSTP). The research determined the difference in the three dimensions of the defined standard among in-service secondary school teachers with respect to gender and location. It was a survey type quantitative study. The population included all the secondary school teachers (SSTs) in the four provinces and Islamabad.